Snakebite Masquerading as Brain Death: A Case Report from Nepal - Balla, Pujan; Baidya, Smriti; Shahi, Kul Raj; Paudel, Khechar Nath (Journal of Institute of Medicine Nepal, 2024)
Neurotoxic envenomation from snake bites, particularly krait bites, can mimic brain death. A 17-year-old male was referred to our hospital intubated, presenting with clinical features consistent with brain death. However, the absence of a clear preceding event and his residence in a snakebite-endemic region raised suspicion of snakebite. Prompt administration of anti-snake venom led to significant recovery, and he was discharged without neurological deficits. This case underscores the need for clinicians to recognize neurotoxic snake bites as a potential differential diagnosis of brain death, particularly in resource-limited endemic areas where diagnostic capabilities may be restricted.